Novel method for the genomic analysis of PKD1 mutation in autosomal dominant polycystic kidney disease - Shang, Shunlai; Wang, Chao; Chen, Lang; Shen, Wanjun; Xie, Yuansheng; Li, Wenge; Li, Qinggang (Frontiers in Cell and Developmental Biology, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disease. Although next-generation sequencing (NGS) technology can be used to sequence tens of thousands of DNA molecules simultaneously. It has poor capture efficiency for the six PKD1 pseudogenes and GC-rich regions. Multiplex ligation-dependent probe amplification (MLPA) technology can detect consecutive deletions of exons, but it is less sensitive for single-base mutations. However, pathogenic genes might not be detected in some patients, even when using the above methods. Improving the detection rate of pathogenic genes is an important technical problem hindering clinical diagnosis of ADPKD. Four pedigrees of ADPKD patients with mutation sites not identified by NGS were examined by other methods. First, MLPA was performed. Then, pedigrees in which MLPA did not identify pathogenic genes were subjected to multiplex polymerase chain reaction (MPCR) and targeted region sequencing. Finally, the detected mutation sites were verified by Sanger sequencing. The results showed that MLPA detected the following PKD1 exonic deletion mutations in three pedigrees: PKD1-18 nt–290 nt, PKD1-up-257 nt, PKD1-up-444 nt and PKD1-3 nt–141 nt. A new mutation site was identified through targeted region sequencing in one pedigree: PKD1 NM_001009944: c.151T > C at the protein level, described as p. Cys51Arg. In summary, we established a system of genetic detection and analytical methods, from NGS to MLPA to targeted region sequencing and finally to Sanger sequencing. We combined MPCR and targeted region sequencing for the first time in ADPKD diagnosis, which further improved diagnosis accuracy. Moreover, we identified one new missense mutation and four new deletion mutations.